Accessing housing, constraints and coping strategies by female-headed households in masvingo, Zimbabwe - Muzvidziwa, Victor N. (Institute of Southern African Studies, 2016)
This article seeks to project the constraints faced by female-headed households in accessing housing, and the strategies, which they adopt to solve this, in a provincial town of Masvingo in southern Zimbabwe. Female-heads of households' relative disadvantage, in gaining access to housing and how they developed coping strategies to deal with this disadvantage is the main focus of the article. A qualitative research design was adopted as the main methodological approach in the study on female heads of households. Multiple research techniques were employed during the data-gathering phase. Informal interviews, observations, documentary sources as well as in-depth interviews were utilized. The main argument presented in the paper is that despite their disadvantaged position in the housing markets, female-heads of households have managed to develop strategies to cope with the inequitable system of housing access. There are however, many challenges and obstacles the women have to overcome in accessing housing for themselves and in some cases their dependents as well. Moser's (1993) concepts of 'practical needs' aimed at improvements in women's everyday life experiences and 'strategic needs' having the capacity to transform gender relations, are useful to an understanding of the strategizing behaviour by the women in relation to accessing housing.